A MODEL LINKING HUMAN RESOURCES MANAGEMENT PRACTICES WITH EMPLOYEE’S COMMITMENT TO CORE VALUES OF AN ORGANISATION - Oluwayemi, Oginni Babalola (Archives of Business Research, 2019)
The focus of the paper was on a model designed to explain the linkage between Human Resources Management practices and employee’s commitment to the core values of business organisation. The model place high premium on the business environment to be the major determinant in whatever happens in the business organisation. The values as well as beliefs and philosophies of founders must be congruent with business environment otherwise attainment of business objective will not be actualised. Similarly, the management of people in workplace through human resources management practices are contingent on human resources management policy which draws its strengths from business objectives and organisational policies. It is therefore evident from the model that where human resources management practices can herald positive perception and image, employees will be loyal and be willing to remain with the organisation over a long period of time thus ensuring commitment to core values of the organisation and the feedback framework is an avenue to evaluate the level of agreement between and among the business environment, employees’ expectations and focus of the organisation.